PERBEDAAN PRESTASI MAHASISWA LULUSAN SMA IPA DENGAN LULUSAN SMA IPS PADA MAHASISWA TINGKAT I DAN II D-III KEBIDANAN UNIVERSITAS BATAM TAHUN 2017 - Pangabean, Rumaita; Mariyana, Mariyana (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Midwifery education merupkan education that learn about sians, education is expected midwives accept students graduates SPR or SMA IPA. The fact that NON IPA high school graduate students are accepted in midwifery affects their learning achievement. This study aims to, note the difference in student achievement of high school graduates IPA with IPS in students of grade I and II D-III Midwifery University of Batam Year 2017. Research design, Comparative study. Sample 46 respondents with technique of sampling purposive sample, data analysis with T-test, research time may-August 2017. the result of the research is 26 graduate students (56,5%) have average higher learning achievement that is 3,37, student of IPS graduates as much as 20 people (43,5%) have average achievement of lower learning that is 3 , 13. based on the T-test test obtained Ï-value 0.003 <0.05, it can be concluded there is a significant difference in learning achievement between high school graduate students IPA and IPS in students of grade I and II D-III midwifery Universitan Batam Year 2017. It is expected that the University is more selective to accept new students, and study program more attention to learning that is easy to understand student.